Double‐blind, randomized phase 3 trial of low‐dose 13‐cis retinoic acid in the prevention of second primaries in head and neck cancer: Long‐term follow‐up of a trial of the Eastern Cooperative Oncology Group‐ACRIN Cancer Research Group (C0590). Issue 23 (7th August 2017) - Bhatia, Aarti K.; Lee, Ju‐Whei; Pinto, Harlan A.; Jacobs, Charlotte D.; Limburg, Paul J.; Rubin, Philip; Arusell, Robert M.; Dunphy, Eamonn P.; Khandekar, Janardan D.; Reiner, Seth A.; Baez‐Diaz, Luis; Celano, Paul; et al.
Abstract : BACKGROUND: 13‐Cis retinoic acid (13‐CRA) is a synthetic vitamin A derivative. High‐dose 13‐CRA in patients with squamous cell cancers of the head and neck (SCCHNs) reduces the incidence of second primary tumors (SPTs). The authors report long‐term results from a phase 3 randomized trial that compared treatment with low‐dose 13‐CRA versus placebo for patients who had early stage SCCHN, with a focus on the development of SPTs and overall survival (OS). METHODS: In total, 176 patients who received treatment for stage I/II SCCHN were randomized to receive either low‐dose 13‐CRA (weight‐based dose of 7.5 mg or 10 mg) or placebo for 2 years. A competing‐risk approach and the log‐rank test were used to compare the time to SPT and OS, respectively, between groups. RESULTS: 13‐CRA neither significantly reduced the cumulative incidence of SPT ( P  = .61) nor improved the time to SPT (hazard ratio [HR] for 13‐CRA/placebo; 0.86; P  = .61). Despite limited power, there was a trend toward improved OS for the 13‐CRA arm (HR, 0.75; P  = .14), particularly among patients whose index tumor was surgically excised (N = 26; HR, 0.50; P  = .057) and among women (N = 39; HR, 0.44; P  = .065) and never/former smokers (N = 129; HR, 0.61; P  = .055), with a median follow‐up of 16 years. The main 13‐CRA related toxicities were dry skin and cheilitis. CONCLUSIONS: Treatment with low‐dose 13‐CRA for 2 years did not decrease the incidence of SPT; subset analysis indicates a potential survival advantage among patients who are women and never/former smokers. More targeted interventions based on clinical risk factors and molecular characterization of tumors may yield greater success in future prevention trials. Cancer 2017;123:4653‐4662 . © 2017 American Cancer Society . Abstract : Effective chemoprevention is an unmet need in head and neck cancers. This study reports on the lowest dose of retinoids ever studied for this indication and provides the longest follow‐up to date.